Mast cell tryptase and asthma - M-Q. Zhang; H. Timmerman (Hindawi Limited, 1997)
Recent physiological and pharmacological studies have indicated the potential importance of tryptase, the major protein component in mast cells, in inflammatory diseases (especially asthma). Being released at inflammatory sites after the activation of mast cells, tryptase is capable of causing bronchohyperresponsiveness and infiltration of eosinophils, neutrophils, etc. in animal airways. The mechanisms by which tryptase causes bronchoconstriction involve probably the potentiation of other chemical mediators such as histamine, production of bradykinin via the hydrolysis of kininogen, and cleavage of the bronchodilating peptides VIP (vasoactive intestinal peptide) and PHM (peptide histidine-methionine). Tryptase has also been found to be a potent mitogen in vitro for airway smooth muscle cells and epithelial cells, implying its role in the hyperplasia of the asthmatic airways. The experimental data providing evidence for the above roles of tryptase are summarized in the present review, as well as the effects of tryptase inhibition in animal asthma models. The potential strategies for the development of anti-asthmatic agents based on the inhibition of tryptase are discussed.